Carbon quantum dots implanted sulfonated 2D-MoS2 for hydrogen evolution - Sarkar, Akash; Ganesh, Gayathry; Qamar, Ummiya; Singh, Vivek Kumar; Sharma, Ruchi; Srivastava, Ankur; Venugopal, Gunasekaran; Rajan, Jose; Das, Santanu (ELSEVIER, 2025)
We report the enhancement of electrocatalytic activity in sulfonate (− SO3H) group functionalized two-dimensional molybdenum disulfide (2D-s-MoS2) nanosheets for their use in hydrogen evolution reaction (HER). These as-developed nanosheets have been decorated with sustainable biomass-derived carbon quantum dots (CQDs) via a sonochemical method, creating a s-MoS2-CQD composite material. This innovative composite demonstrates significantly improved electrocatalytic performance for the hydrogen evolution reaction (HER) via water splitting. In particular, incorporating CQDs on 2D-s-MoS2 overcomes many limitations, as observed in pristine 2D-MoS2 and 2D-s-MoS2, especially regarding low electrical conductivity and restricted electrocatalytic activity on the basal plane. Incorporating CQDs enhances electron transfer efficiency, increases the availability of active sites, and enhances overall conductivity. As a result, the s-MoS2-CQD achieves remarkable HER performance, featuring a lower overpotential of ~ 273 mV and a reduced Tafel slope of 67 mV/dec compared to s-MoS2. These enhancements signify faster reaction kinetics, accelerated H* adsorption–desorption, and greater catalytic efficiency. Furthermore, using sustainably synthesized CQDs positions this approach as a cost-effective, scalable, and environmentally friendly alternative to traditional noble-metal catalysts. This research highlights the potential of functionalized twodimensional materials, such as s-MoS2, implanted with zero-dimensional materials, such as CQDs, to advance sustainable hydrogen production technologies, thereby contributing to the global shift towards clean energy solutions.